Facile Formation of Anatase/Rutile TiO2 Nanocomposites with Enhanced Photocatalytic Activity - He, Jing; Du, Yi-en; Bai, Yang; An, Jing; Cai, Xuemei; Chen, Yongqiang; Wang, Pengfei; Yang, Xiaojing; Feng, Qi (Molecules (Basel, Switzerland), 2019)
Anatase/rutile mixed-phase TiO2 nanoparticles were synthesized through a simple sol-gel route with further calcination using inexpensive titanium tetrachloride as a titanium source, which effectively reduces the production cost. The structural and optical properties of the prepared materials were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and UV-vis adsorption. The specific surface area was also analyzed by Brunauer–Emmett–Teller (BET) method. The anatase/rutile mixed-phase TiO2 nanocomposites containing of rod-like, cuboid, and some irregularly shaped anatase nanoparticles (exposed {101} facets) with sizes ranging from tens to more than 100 nanometers, and rod-like rutile nanoparticles (exposed {110} facets) with sizes ranging from tens to more than 100 nanometers. The photocatalytic activities of the obtained anatase/rutile mixed-phase TiO2 nanoparticles were investigated and compared by evaluating the degradation of hazardous dye methylene blue (MB) under ultraviolet light illumination. Compared to the commercial Degussa P25-TiO2, the mixed-phase TiO2 nanocomposites show better photocatalytic activity, which can be attributed to the optimal anatase to rutile ratio and the specific exposed crystal surface on the surface. The anatase/rutile TiO2 nanocomposites obtained at pH 1.0 (pH1.0-TiO2) show the best photocatalytic activity, which can be attributed to the optimal heterojunction structure, the smaller average particle size, and the presence of a specific exposed crystal surface. The enhanced photocatalytic activity makes the prepared anatase/rutile TiO2 photocatalysts a potential candidate in the removal of the organic dyes from colored wastewater.